2023
DOI: 10.1371/journal.pone.0291452
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of possible sarcopenia in patients with subacute stroke

Yeo Hyung Kim,
Young-Ah Choi

Abstract: Possible sarcopenia, the loss of handgrip strength in the older population, can lead to poor functional prognosis after stroke. In this retrospective study, we aimed to elucidate the clinical risk factors for possible sarcopenia at discharge in 152 hospitalized patients with subacute stroke. Univariable and multivariable logistic regression analysis was performed to determine the risk factors associated with possible sarcopenia. At the time of discharge, the prevalence of possible sarcopenia was 68.4%. After a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Further, a high sarcopenia prevalence has been reported in patients with heart failure 18 or who originally had a stroke, 19 with a remarkable surge in prevalence following a stroke event 20 . Previous studies have reported a 68.4% prevalence of “possible sarcopenia” in inpatients with subacute stroke at discharge, 21 which is higher than that in community‐dwelling older adults or outpatients 22,23 . This implies an increased propensity for sarcopenia and “possible sarcopenia” with prolonged poststroke duration or greater disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…Further, a high sarcopenia prevalence has been reported in patients with heart failure 18 or who originally had a stroke, 19 with a remarkable surge in prevalence following a stroke event 20 . Previous studies have reported a 68.4% prevalence of “possible sarcopenia” in inpatients with subacute stroke at discharge, 21 which is higher than that in community‐dwelling older adults or outpatients 22,23 . This implies an increased propensity for sarcopenia and “possible sarcopenia” with prolonged poststroke duration or greater disease severity.…”
Section: Discussionmentioning
confidence: 99%